2001
DOI: 10.2527/2001.7961359x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, physical, and environmental properties of pelleted newspaper compared to wheat straw and wood shavings as bedding for horses.

Abstract: Two experiments were conducted comparing pelleted recycled newspaper (PN) to wheat straw (S) and kiln-dried pine wood shavings (WS) as an animal bedding material. Adult horses housed 20 to 21 h/d in boxstalls served as the animal model for comparisons. In Exp. 1 eight boxstalls, each housing one horse, were each bedded with two types of PN (0.32 and 0.64 x 2.54 cm), S, and WS over four 5-d periods (replicated 4 x 4 Latin square). Initial amounts of bedding materials surpassed most commercial conditions, but st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 8 publications
1
19
0
1
Order By: Relevance
“…Wood chip bedding is a mixture of bark, post peelings, and sawdust with a greater portion of materials <5 mm in size (Ward et al, 2000). In addition, wood chips offer greater water holding capacity (Ward et al, 2000), require less frequent addition as bedding (Ward et al, 2001), and keep animals cleaner (McAllister et al, 1998) compared with straw. Moreover, recent drought on the Canadian prairies has decreased the supply (and increased the cost) of straw for livestock bedding, making wood chips a more economically viable alternative.…”
mentioning
confidence: 99%
“…Wood chip bedding is a mixture of bark, post peelings, and sawdust with a greater portion of materials <5 mm in size (Ward et al, 2000). In addition, wood chips offer greater water holding capacity (Ward et al, 2000), require less frequent addition as bedding (Ward et al, 2001), and keep animals cleaner (McAllister et al, 1998) compared with straw. Moreover, recent drought on the Canadian prairies has decreased the supply (and increased the cost) of straw for livestock bedding, making wood chips a more economically viable alternative.…”
mentioning
confidence: 99%
“…In previous reports (Kosuge et al . 2000; Ward et al . 2001), it was shown that rice straw has a water suction rate lower than the other bedding materials, and urea‐adhering straw is a fertile environment for mold.…”
Section: Discussionmentioning
confidence: 99%
“…When pelleted newspaper, straw and wood shavings are used as bedding material, pelleted newspaper and wood shavings have water suction rates higher than straw, thereby reducing the need for the replacement of bedding material and making it more practical. However, regarding the bedding material environment in stalls, the rise in pH is highest for pelleted newspaper, and lowest for straw (Ward et al . 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have observed the effectiveness and performance of various absorbent materials as animal beddings, such as straw (cereal straw), woodchip (sawdust, bark or wood shavings), bracken and rushes (Schofield, 1988;Deininger et al, 2000;Ward et al, 2000;Ward et al, 2001;Vinten et al, 2006;Molnar & Wright, 2006). But the list of absorbent materials is variable.…”
Section: Introductionmentioning
confidence: 99%
“…But the list of absorbent materials is variable. In other countries, for example, green cuttings, farm-hedge trimmings, waste shredded newspaper, chopped cardboard, plasterboard backing paper, zeolite, shredded bricks, shredded chestnuts, coir, pea haulm, oilseed rape straw, canary reed grass, miscanthus and peat moss, are also widely used (Ward et al, 2001;Pohl, 2002;HCC, 2010;Logan, 2011).…”
Section: Introductionmentioning
confidence: 99%